Microvesicle-Shuttled microRNA-130b Activates the Hepatic Inflammation by Inhibiting Glucocorticoid-Receptor-Mediated Immunosuppression in High-Fat Diet-Induced Obese Mice - Zhengqiang Han; Lijun Wang; Shiyong Xu; Horsen Zhang; Ji Cheng; Shifeng Pan (Veterinary Sciences)
Metabolism-disorder-induced liver diseases have become increasingly prevalent worldwide and are clinically linked to obesity and type 2 diabetes. In addition, a large number of previous literature studies have indicated that plasma miR-130b is a promising biomarker for the early diagnosis and treatment of obesity. However, whether miRNA-130b that was positively correlated with obesity resulted in hepatic inflammation needs to be further studied. Therefore, the study aims to determine the effect of microvesicle-shuttled miRNA-130b (miR-130b-MV) on the hepatic inflammation and its potential mechanism in high-fat diet-induced obese mice. Three-week-old C57BL/6 mice were fed a high-fat diet for eight weeks. Then, the obese mice received tail vein injections of MV-packaged scrambled control microRNA (miR-SC-MV) or miR-130b-MV every other day for 10 days. Compared with the control group, the miR-130b-MV injection significantly reduced the body weight while increasing the ratio of liver wet weight to total body weight. In addition, the miR-130b-MV injection significantly activated the hepatic inflammation by increasing the expression of proinflammatory genes, although the plasma concentrations of IL-6 and TNF-α were only slightly increased. Furthermore, the miR-130b-MV injection significantly increased the hepatic miR-130b expression while significantly suppressing the protein expression and phosphorylation of GR, a potential target of miR-130b. Moreover, the miR-130b overexpression results in a decrease in the expression of endogenous GR protein and a decrease in the activity of the luciferase reporter of GR 3′-UTR. In addition, the miR-130b-MV injection significantly upregulated NF-kB (p50) in both the cytoplasm and nucleus, showing enhanced proinflammation response. The above results demonstrated that miR-130b-MV activated the hepatic inflammation by inhibiting GR-mediated immunosuppression in high-fat diet-induced obese mice, suggesting a novel mechanism underlying the obesity-induced hepatic inflammation, and the inhibition of miR-130b may serve as a new molecular therapeutic target for the prevention and treatment of hepatic inflammation.